The reuse of tombs in Eastern Arabia - Döpper, Stephanie (Arabia Orientalis, 2023)
This text investigates the reuse of tombs in Eastern Arabia from the beginning of the Early Bronze Age until the end of the Sasanian period in order to understand the underlying purposes and social context of this practice